Attempt of Interpretation of Marx trough Marx rather than Marxism’s - Rakadjiyska, Temenuga (Research Papers, 2019)
This article broadly focuses on some cardinal achievements in Marx's creative heritage. The basic guiding principle in its writing is the observation of the principle adopted by him in "The Capital" – “the way of exposure formally has to be distinguished by the way of the research”.  Of course, by an attempt for a comprehensive reading of his creativity in order to explicate his critical approach to analyzing the capitalist conditions of production and reproduction of people’s social life.
Keywords: Capital; Marx's creative heritage; Dialectical logic and critique; Surplus value; Politics and ideology